2020
DOI: 10.48550/arxiv.2010.14527
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GWTC-2: Compact Binary Coalescences Observed by LIGO and Virgo During the First Half of the Third Observing Run

R. Abbott,
T. D. Abbott,
S. Abraham
et al.

Abstract: UTC. By imposing a false-alarm-rate threshold of two per year in each of the four search pipelines that constitute our search, we present 39 candidate gravitational wave events. At this threshold, we expect a contamination fraction of less than 10%. Of these, 26 candidate events were reported previously in near real-time through GCN Notices and Circulars; 13 are reported here for the first time. The catalog contains events whose sources are black hole binary mergers up to a redshift of ∼ 0.8, as well as events… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
808
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(830 citation statements)
references
References 260 publications
21
808
0
1
Order By: Relevance
“…Integrals involving M k were approximated as Monte Carlo integrals. For the prior probability π(m 1 , m 2 ) we adopted the average over the posterior population distribution of the model fit on the GWTC-2 gravitational wave catalog (power law + peak model; Abbott et al 2021). This model takes into account the mass distributions for both black holes, including the correlation between them Talbot & Thrane 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Integrals involving M k were approximated as Monte Carlo integrals. For the prior probability π(m 1 , m 2 ) we adopted the average over the posterior population distribution of the model fit on the GWTC-2 gravitational wave catalog (power law + peak model; Abbott et al 2021). This model takes into account the mass distributions for both black holes, including the correlation between them Talbot & Thrane 2018.…”
Section: Resultsmentioning
confidence: 99%
“…The era of gravitational wave (GW) astronomy has begun with the first detection of a binary black hole (BBH) merger in 2015 (Abbott et al 2016). There have been ∼ 90 BBH systems discovered with ∼ 3 years observation in the LIGO/Virgo O1/O2/O3 runs (GWTC-1&2 catalogues: Abbott et al (2019Abbott et al ( , 2020). The number is catching up on that of the discovered Galactic black holes (BH) in Xray binaries during the last half century (Corral-Santana et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Type Ic supernovae with broad lines in the spectra are typically found in metal-poor hosts, whereas normal Type Ic supernovae avoid dwarf galaxies (Modjaz et al 2011). It has been suggested that BHs with masses above ∼ 30 M , frequently found in binary BH mergers detected in GW by LIGO/Virgo (Abbott et al 2020), may originate from metal-poor environments, where the reduced strength of line-driven winds allows for the formation of more massive BHs (e.g. Belczynski et al 2010;Vink et al 2021).…”
Section: Introductionmentioning
confidence: 99%